Control of a robotic exoskeleton for children lower limb rehabilitation - Pérez, R.; Salgado, I.; Chairez, I. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2017)
This manuscript describes the instrumentation and control of an exoskeleton prototype to improve the rehabilitation of children between 5 and 8 years old. The prototype has the characteristic of being programmable with different rehabilitation tasks traduced in several rehabilitation pathways defined by medical specialists. The control strategy was to achieve the desired movements associated to medical therapies, which are obtained by a discrete-time proportional derivative controller. The instrumentation includes the use of an 32-bits ARM processor that performed all the desired trajectories as well as the decentralized control strategies proposed for the exoskeleton. Experimental results show the behavior of the robotic exoskeleton fulfilling the expected movements for the proposed tracking signal reference.